2019
DOI: 10.1021/jacs.9b04337
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Molecular Architecture and Adsorption Density on Adhesion of Mussel-Inspired Surface Primers with Catechol-Cation Synergy

Abstract: Marine mussels secrete proteins rich in residues containing catechols and cationic amines that displace hydration layers and adhere to charged surfaces under water via a cooperative binding effect known as catechol-cation synergy. Mussel-inspired adhesives containing paired catechol and cationic functionalities are a promising class of materials for biomedical applications, but few studies address the molecular adhesion mechanism(s) of these materials. To determine whether intramolecular adjacency of these fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 39 publications
6
39
1
Order By: Relevance
“…Surprisingly, we did not observe a substantial increase in the dry and wet failure times as compared to PSA‐DAc. Unlike the behavior noted at the molecular level in this study and recent SFA measurements by others, the static shear test results indicate that close proximity of cation‐aromatic binding pairs can significantly affect the macroscopic cohesive strength. The results might also explain why marine mussels have evolved to secrete adhesive proteins with Dopa and Lys pairs located mostly adjacent to each other rather than separated by spacer amino acids such as glycine.…”
Section: Resultscontrasting
confidence: 98%
See 2 more Smart Citations
“…Surprisingly, we did not observe a substantial increase in the dry and wet failure times as compared to PSA‐DAc. Unlike the behavior noted at the molecular level in this study and recent SFA measurements by others, the static shear test results indicate that close proximity of cation‐aromatic binding pairs can significantly affect the macroscopic cohesive strength. The results might also explain why marine mussels have evolved to secrete adhesive proteins with Dopa and Lys pairs located mostly adjacent to each other rather than separated by spacer amino acids such as glycine.…”
Section: Resultscontrasting
confidence: 98%
“…The trend observed in CPS measurements is similar to what was noted earlier in SMFS experiments and can indicate that architecture of the polymer and the adjacency of catechol‐ and amine‐containing groups might not be necessary in establishing the cooperative effects to improve the adhesion, at least when measured at the microscopic or molecular levels. Similar observations have been made recently by Degen et al., where results of SFA measurements implied that incorporating glycine residues as spacer between the cationic and catecholic groups did not lead to significant changes in the force required to separate peptide‐coated mica surfaces.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…For instance, a large number of positively charged Lys or arginine (Arg) residues are found in proximity to DOPA along the protein backbone 23 . Recently, Maier et al and others utilized surface forces apparatus (SFA) to study the adaptive synergy between amine and catechol in binding to wet mica, using small molecule cyclic analogs with Lys or Arg present adjacent to catechol or phenyl groups 1,24,25 . Their results showed that adhesion energy is remarkably higher when both catechol and amine are present, suggesting a synergistic effect between these functional motifs.…”
mentioning
confidence: 99%
“…[24,25] It is known that the proteins secreted by various organisms such as mussels and sandcastle worms demonstrate robust adhesion performance under different conditions. [26][27][28][29][30][31] Through the analysis of their protein structures, large amount of 3,4-dihydroxy-L-phenylalanine (DOPA) moieties are found in these proteins that play a crucial role for their adhesion performance due to the diversity of catechol chemistry. [32][33][34][35][36] Traditionally, mussel foot proteins (Mfps) are extracted directly from mussel foot filaments, which is expensive owing to the high production costs and low extraction efficiency.…”
Section: Introductionmentioning
confidence: 99%